PENINGKATAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING BERBANTU MEDIA FLASHCARD PADA SISWA KELAS V SDN 90/II TALANG PANTAI - Eni Rosita Sari Kustriyana; Randi Eka Putra; Subhanadri (STKIP Subang, 2025)
The problem in this research is the low motivation and learning outcomes of students in mathematics in grade V of State Elementary School 90/II Talang Pantai. This research is a classroom action research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of this research were 21 students, and it was carried out in the first semester of the 2025 academic year. Data collection techniques used teacher observation sheets, student observation sheets, and test questions. The student motivation questionnaire data shows a significant increase, where in cycle I it was recorded at 71.42%, and then increased to 95.23% in cycle II. This increase reflects that students are becoming more motivated in participating in learning along with the improvement of the strategies applied. The research results show that the contextual teaching and learning approach is able to improve student motivation and learning outcomes. This is evident from the increase in the percentage of teacher involvement in teaching from 66.66% in cycle I to 73.33% in cycle II. Meanwhile, student involvement in the learning process increased from 52.38% to 100%. A significant increase was also seen in the completeness of student learning outcomes, from 71.42% in cycle I to 85.71% in cycle II. It can be concluded that the application of the contextual teaching and learning approach can increase student activeness and cooperation, thereby developing their scientific process and improving the achievement of student learning outcomes